PENERAPAN METODE VAKT UNTUK MENINGKATKAN KETERAMPILAN TARI LILIN PADA SISWA TUNARUNGU DI SKH BINA CITRA ANAK - Sri Amalia Ningsih; Toni Yudha Pratama; Yuni Tanjung Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Deaf students often experience difficulties in learning dance skills, particularly in understanding and performing movement sequences accurately. This study aimed to examine the effect of the VAKT (Visual, Auditory, Kinesthetic, and Tactile) method on the candle dance skills of deaf students at SKh Bina Citra Anak. A pre-experimental method with a one-group pretest-posttest design was employed involving five deaf students as research participants. Data were collected through pre-tests and post-tests using a candle dance performance assessment instrument to measure students' progress after receiving instruction through the VAKT method. The findings indicated that the students demonstrated strong initiative and active engagement throughout the learning process, including the pre-test, treatment, and post-test stages. The implementation of the VAKT method improved students' ability to perform dance movements in a more structured, accurate, and coordinated manner. Wilcoxon signed-rank test analysis revealed that the calculated value (Tcount = 15) was greater than the critical value (Ttable = 0), leading to the rejection of H0 and acceptance of Ha. These findings confirm that the VAKT method has a positive effect on improving the candle dance skills of deaf students. The integration of visual, auditory, kinesthetic, and tactile elements facilitates students' understanding of dance movements through demonstrations, physical practice, and tactile experiences, making the learning process more effective and appropriate for the characteristics of deaf learners.